A Polynomial Current Controller for a Third-Harmonic Modulated Power Factor Correction Rectifier Feeding a Vector Controlled Induction Motor Drive. Issue 2 (20th January 2017) - Singh, Bhim; Gurumoorthy, Bhuvaneswari; Madishetti, Sandeep
Abstract: This paper presents the analysis, design, and hardware implementation of a digital polynomial Regulation, Steady-State Error and Tracking (RST) current controller-based third-harmonic modulated boost-type power factor correction (PFC) rectifier. The proposed rectifier is used at the front end of a vector controlled induction motor drive (VCIMD) to eliminate harmonics at the input AC supply. The proposed PFC rectifier modifies the input current to a sinusoid with unity power factor apart from offering DC bus voltage regulation. In this paper, a digital proportional-integral (PI) and RST current controllers are compared in terms of total harmonic distortion (THD) and power factor (PF) at the point of common coupling for different loading conditions. The RST current controller tracks the set-point accurately with zero steady-state error and offers good disturbance rejection that enables further reduction of supply current THD as compared to a conventional PI current controller. The control algorithm for the PFC front end rectifier along with vector control technique is implemented using a digital signal processor, and the dynamic performance is analyzed for step changes in reference speed and load torques, demonstrating significant improvement in the performance indices.